APPLICATION OF IMAGE MEDIA IN ARABIC VOCABULARY WRITING SKILLS - Gusti Muhammad Alfarizi; M. Ramli (International Journal of Multidisciplinary Reseach, 2025)
This study aims to describe learning media in the form of pictures can be a support for students in the Arabic language learning process, Pictures are one of the learning media and teaching materials, Image media is a learning resource and teaching materials that can make learning more contextual, concrete, meaningful, in accordance with the constructivist learning paradigm. With picture media, it will overcome the difficulty of writing Arabic vocabulary in class IV MI Nurul-Huda Banjarmasin. In addition, this study also aims to analyze the writing ability of Nurul Huda Banjarmasin students after using picture media as a learning stimulus. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The data was analyzed using an interactive analysis model. The results of the study showed that learning planning was prepared with a structured syllabus and lesson plans. The implementation of learning uses a series of pictures media as many as five pictures to stimulate students' creativity and imagination in writing. Image media has proven to be effective as a visual aid that can facilitate students in expressing ideas in writing, strengthen their understanding of language structure, and increase their interest and motivation to learn. Thus, image media can be used as a strategic alternative in teaching writing skills in Arabic language learning.